2020
DOI: 10.7759/cureus.11568
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Gastric Emphysema: Incidental Findings or Serious Illness

Abstract: Gastric emphysema (GE) or gastric pneumatosis is a rare entity defined as air within the gastric wall. Etiologies include pneumothorax, instrumentation, infection, gastric wall ischemia, and mechanical injury. Several theories exist as to how the air disrupts the integrity of the gastric wall. These include a bacterial infection with Clostridium species and other gas-forming aerobic colonic bacilli, instrumentation with direct submucosal gastric wall injury, mechanical injury following increased intra-abdomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The differentiation between emphysematous gastritis and gastric emphysema can be challenging but is important as clinical outcomes are totally different and indication for surgical treatment can vary. 5 Recent studies reported on the successful conservative treatments including fluid resuscitation, broad-spectrum antibiotics, bowel rest, fluid hydration and total parenteral nutrition. Surgical removal of the ischaemic gastric area by total gastrectomy or partial gastrectomy may be considered for patients with evidence of transmural ischemia, peritonitis or haemodynamic instability despite appropriate resuscitation.…”
Section: Images In…mentioning
confidence: 99%
“…The differentiation between emphysematous gastritis and gastric emphysema can be challenging but is important as clinical outcomes are totally different and indication for surgical treatment can vary. 5 Recent studies reported on the successful conservative treatments including fluid resuscitation, broad-spectrum antibiotics, bowel rest, fluid hydration and total parenteral nutrition. Surgical removal of the ischaemic gastric area by total gastrectomy or partial gastrectomy may be considered for patients with evidence of transmural ischemia, peritonitis or haemodynamic instability despite appropriate resuscitation.…”
Section: Images In…mentioning
confidence: 99%